A Critical Approach to the Studies of Political Thought in the History of Iran; The Critique on the Book Advice Paradigm, Iranian Thought Beyond Decline and Continuity - Nayere Dalir (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
“Advice Paradigm, Iranian Thought Beyond Decline and Continuity”, the book of Iranian thought strives to combine the writings of the ancient and Islamic periods in a single pattern; includes and analyzes “the two dilemmas” and “the four implications”. The question is what the model of the authors of the paradigm of advice is; for explaining the epistles of Iranian history and to what extent it is sufficient for the theoretical studies of this group of historical sources? The findings of the research, which have been done using a critical approach and the historical explanation method, show that the basis of the ideas of the book is based on a predetermined framework, and is influenced by the reproduced Iranshahri theory of the contemporary period. In a critical evaluation, what is expected is the possibility of proposing a different model for reading the texts of the Political Epistles.